A Critique and Refinement of the Wakefieldian Concept of Disorder: An Improvement of the Harmful Dysfunction Analysis. Issue 4 (5th November 2022) - Smith, Emmanuel
Abstract: One way in which bioethicists can benefit the medical community is by clarifying the concept of disorder. Since insurance companies refer to the DSM for whether a patient should receive assistance, one must consider the consequences of one's concept of disorder for who should be provided with care. I offer a refinement of Jerome Wakefield's hybrid concept of disorder, the harmful dysfunction analysis. I criticize both the factual component and the value component of Wakefield's account and suggest how they might be improved. I propose that the factual component should be statistical variation analyzed in multilevel and chronological compilations of physiological data. I propose that the value component should prioritize the individual's authority regarding the experience of suffering from a physiological condition. My account preserves the insight of using a factual and a value component while avoiding the problems that Wakefield's original account faces.